Dark Deception - Mehl, Nancy (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2017)
"Four years ago, Kate O'Brien and her twin were attacked by a serial killer and only Kate survived. She's been in witness protection ever since her testimony led to a conviction. When new evidence is found suggesting they got the wrong man, Kate is terrified. With a target on her back, can U.S. Marshal Tony DeLuca keep her safe until the new trial begins?"--Amazon.com.
Keywords: Witnesses -- Fiction -- Protection; Murder victims' families -- Fiction; Serial murderers -- Fiction; Thrillers (Fiction); Christian fiction